Macroeconomic Determinants of Indonesian Economic Growth: Error Correction Model approach for the 1986-2022 period - Wahyuni, Hesti Asri; Santosa, Purbayu Budi (Trunojoyo University of Madura, 2024)
This study analyzes the impact of exports, inflation, investment, and exchange rates on Indonesia's Gross Domestic Product (GDP) from 1986 to 2022 using the Error Correction Model (ECM). This method examines both long-term and short-term effects. The results show that exports have a positive but insignificant impact on long-term economic growth, while in the short term, the impact is negative and insignificant. Inflation has a significantly negative effect on economic growth in both the short and long terms. Investment has a positive and significant effect on growth in both periods. Exchange rates have a significant negative effect on long-term economic growth, while in the short term, they have a significant negative impact at the 10% significance level. The contribution of this study lies in expanding the understanding of Indonesia's macroeconomic dynamics through a comprehensive analysis over a 36-year period. It provides valuable insights for economic policymakers, recommending stabilizing inflation, increasing investment, and maintaining exchange rate stability. The empirical findings of this study are expected to help formulate more effective economic policies to promote growth in Indonesia. A limitation of this research is the lack of variables addressing external factors, including global fiscal and monetary policies.